YOUNG CLINICIANS’ FORUMCorrelation between mixed venous blood saturation and cardiac output in patients undergoing cardiac surgery procedures - Szurlej, Bartosz; Piekarska, Magda; Szurlej, Dariusz; Węglarzy, Andrzej; Latusek, Tomasz; Bachowski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background : The physiological reaction to a decrease of cardiac output (CO) is an increase of oxygen extraction. Patients with compromised circulation often are not capable of this reaction. The oxygen concentration in such cases will not change with respect to the CO; therefore the mixed venous blood saturation (SvO 2 ) will not be a reliable indicator of the blood flow. Aim of the study : The aim of the study was to determine the reliability of the correlation between hemodynamic parameters and indices of tissue oxygenation in patients undergoing cardiac surgery procedures. Material and methods : We performed a retrospective analysis in 19 patients who required Swan-Ganz catheter (SGC) insertion. Measurements were taken at three time points. Values of cardiac index (CI), mixed venous oxygen saturation (SvO 2 ), oxygen uptake (VO 2 ), oxygen extraction ratio (O2ER), and base excess (BE) were analyzed and compared with oxygen partial pressure (PaO 2 ), carbon dioxide partial pressure (PaCO 2 ) and arterial blood saturation (SaO 2 ). Results: Our study revealed an increase of CI, VO 2 and O 2 ER and a decrease of SvO 2 after the operation in comparison with the preoperative period. There was a positive correlation between the trends of SvO 2 and CI before and after the surgery. Conclusions: Correct values of SaO 2 , PaO 2 and PaCO 2 do not mean that the level of subcellular processes associated with the extraction of oxygen proceed in a physiological way. Only SvO 2 and CI results obtained with the SGC make it possible to assess the delivery of oxygen and its consumption at the tissue level.